Adhesion interaction between atomically defined tip and sample - CROSS, GRAHAM (American Physical Society, 1998)
We have measured forces between an atomically defined W(111) tip and an Au(111) sample in ultrahigh vacuum at 150 K. The W tips are manipulated and characterized on an atomic scale both before and after sample approach by field ion microscopy. Forces between the tip and the sample are measured by an in situ differential interferometer. We observe strong attractive adhesion forces, which turn repulsive upon the further approach of the tip towards the Au surface. Unexpected for a metallic system, there is no spontaneous jump to contact. The force versus tip-sample distance curve shows only modest hysteresis, and the field ion microscopy images reveal an atomically unchanged tip apex.
PUBLISHED
Keywords: Physics